Synthesis of biocompatible coating on Ni-Cr alloy by cathodic cage plasma processing technique as anti-pathogenic bacteria for medicinal applications. (1st May 2023) - Asghar, Muhammad; Yousaf, Muhammad; Huwaimel, Bader; Iqbal, Tahir; Ahmed, Irfan; Qureshi, Muhammad Tauseef; Abrar, Muhammad; Shafiq, Muhammad; Almohammedi, Abdullah; Hameed, Reda Abdel; AlElaimi, Mahmoud; Maryam, Mishaal; et al.
Abstract: The current research work reports the deposition of titanium-based multilayer coating (TiO/TiN) on Ni-Cr metallic alloy by a cathodic cage plasma processing technique using a titanium cage along with various combinations of gas mixtures i.e., N2 -H2 -Ar-O2 at 400 °C. The samples were characterized using x-ray photoelectron spectroscopy (XPS), which revealed the surface coating of TiO/TiN with Ti 2p at 462 eV, N 1s at 406 eV and O 1s at 530.09 eV. The x-ray diffraction (XRD) analysis confirmed the polycrystalline structure in the titanium-based coating with (111) for TiO/TiN and a crystallite size of 32 nm. Scanning electron microscopy (SEM) and x-ray dispersive spectroscopy (EDX) analysis of titanium-based TiO/TiN coatings was well correlated with the above mentioned findings. Corrosion analysis using polarization potentio-dynamic plots (PDP) and electrochemical impedance spectroscopy (EIS) revealed a significant improvement in various corrosion parameters like corrosion resistance, corrosion rate, surface porosity, corrosion protection efficiency, impedance, and charge transfer resistance. A spectrophotometer was used to measure the leaching of toxic ions (Ni, Cr) from untreated and treated specimens in NaCl electrolyte. Findings revealed efficient antibacterial activity of TiO/TiN-coated specimens against E. coli and S. aureus as compared to untreated samples. This work will be helpful for understanding the biological features of metallic materials for medicinal applications.